Learning impairments of hippocampal-lesioned mice in a paddling pool. - Deacon, R; Rawlins, J (2002)
Control mice rapidly learned to escape from shallow water in a paddling pool, which combined elements of the Morris water maze and the Barnes holeboard maze. The pool's transparent perimeter wall contained 12 exits, only 1 of which led to an escape tunnel. Learning was impaired in mice with cytotoxic lesions of the hippocampus. Probe trials suggested that the controls were using extramaze cues. When the exit was blocked, controls, but not hippocampals, spent more time searching in this previously correct sector. When the spatial location of the exit was changed, hippocampals escaped more quickly, as they showed no preference for the old location. These results may be useful in the assessment of hippocampal dysfunction, particularly in genetically manipulated mice.